2004
DOI: 10.1038/sj.bjp.0705591
|View full text |Cite
|
Sign up to set email alerts
|

Protection by antioxidants against toxicity and apoptosis induced by the sulphur mustard analog 2‐chloroethylethyl sulphide (CEES) in Jurkat T cells and normal human lymphocytes

Abstract: 1 The mechanism of toxicity of sulphur mustard was investigated by examining the biochemical effects of the analog 2-chloroethylethyl sulphide (CEES) in both human Jurkat cells as well as normal human lymphocytes. 2 Exposure of both types of cells to CEES resulted in a marked decrease in the intracellular concentration of the reduced form of glutathione (GSH), and CEES-induced cell death was potentiated by L-buthionine sulphoximine, an inhibitor of GSH synthesis. 3 CEES increased the endogenous production of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 34 publications
(34 reference statements)
3
39
0
Order By: Relevance
“…In the present study, we showed that GSPE treatment significantly reduced the cleavage of caspase-3 induced by histones stimulation which is consistent with the anti-apoptotic effect of GSPE previously observed in the perfluorooctanoic acid-induced hepatotoxicity model (Liu et al, 2016). In addition, several other natural antioxidants, such as Bauhinia championii flavone, cyanidin-3-glucoside, and N -acetyl cysteine (NAC) have been previously reported to exert anti-apoptotic effects in cardiomyocytes (Jian et al, 2016), neurons (Ke et al, 2011), and human lymphocytes (Han et al, 2004), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we showed that GSPE treatment significantly reduced the cleavage of caspase-3 induced by histones stimulation which is consistent with the anti-apoptotic effect of GSPE previously observed in the perfluorooctanoic acid-induced hepatotoxicity model (Liu et al, 2016). In addition, several other natural antioxidants, such as Bauhinia championii flavone, cyanidin-3-glucoside, and N -acetyl cysteine (NAC) have been previously reported to exert anti-apoptotic effects in cardiomyocytes (Jian et al, 2016), neurons (Ke et al, 2011), and human lymphocytes (Han et al, 2004), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…With similar toxic effects to SM, CEES is a useful SM surrogate used to generate injury models and identify treatment agents [15, 24, 28]. However, it is a monofunctional alkylating agent and a less toxic analog of SM that forms adducts instead of cross-links with cellular molecules [10].…”
Section: Discussionmentioning
confidence: 99%
“…The monofunctional analog of SM, 2-chloroethyl ethyl sulfide (CEES), is extensively used to examine the toxic effects of SM including its DNA damaging properties [15-18]. Like SM, the DNA damage produced by CEES is also reported to be due to its direct alkylating effects, and increased ROS production, that leads to comparable toxic lesions from both these agents [10, 15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depletion of intracellular stores of GSH plays an important role in protecting against oxidative stress by reacting directly with ROS [37][38][39] and NO. 40) Moreover, pretreatment with HT significantly restores the GSH level reduced by t-BHP treatment in HepG2 cells.…”
Section: )mentioning
confidence: 99%